THE ROLE OF EXTENDED FAMILIES IN CAREGIVING FOR THE CHILDREN OF INDONESIAN MIGRANT WORKERS IN COMPRENG VILLAGE, SUBANG REGENCY - Utami, Ratnasari Putri; Hayati, Ashlihul (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The departure of Indonesian Migrant Workers (PMI) affects the care of the children left behind, prompting extended families to often take over the role of parents. This study aims to analyze the role of extended families in caring for the children of PMIs, focusing on aspects of socialization, daily caregiving, socio-psychological support, education, and financial management. Using a qualitative case study approach, data were collected through in-depth interviews and observations with five informants, including PMI children, extended family caregivers, PMIs, and school teachers. The findings indicate that the extended family serves as a substitute secure base, supporting the children’s growth and development through the development of social skills, fulfillment of basic needs, educational assistance, and assurance of financial sustainability. In addition, the extended family plays a role in maintaining the child’s emotional connection with their parents through long-distance communication, although limited resources and consumerist spending patterns in some families remain challenges. This study provides recommendations for extended families, the government, and educational institutions to strengthen the caregiving capacity for PMI children through training, psychosocial assistance, and sustainable financial management.